Immunological features of umbilical cord blood of newborns born to women with different implementation of intrauterine infection - Vygovskaya, Ludmila Anatoliivna (Annals of Mechnikov’s Institute, 2020)
Introduction. Perinatal infections (PNIs) have been increasingly referred to as one of the causes of adverse effects of pregnancy recently, accompanied by an inflammatory process, which is based on a highly integrated immune response. Immunopathological reactions cause destabilization of the whole homeostasis and create a favorable basis for the periodic exacerbation of infectious and inflammatory diseases, and the inability of the pregnant woman’s body to adequate immune response is the cause of the pathological course of pregnancy. Determination of immunological parameters in the umbilical cord reflects the degree of formation of the immune system of the fetus and thus characterizes the level of anti-infective protection, which depends on the risk of infectious abnormalities. Objective: To investigate the immunological features of umbilical cord blood of newborns born to women with different implementation of intrauterine infection (IUI). Materials and methods. The study involved examination of 180 pregnant women divided into 3 groups depending on the presence and nature of the detected infection: Group I - viral (CMV, herpes simplex virus types1,2,6), Group II - bacterial (chlamydia, ureaplasma, mycoplasma) and Group III - mixed (viral and bacterial) infection. Each of these groups was divided into 2 subgroups: with subsequent implementation of the infection in newborns (1) and without it (0). This group was the main one in the study. Control group included 50 patients with physiological pregnancy. In clinical trials, samples of umbilical blood obtained during childbirth from women with signs of IUI after the use of different treatment regimens depending on the etiological factor of PNI were studied. Results and discussion. Studies have shown a significant decrease in the total number of CD3+T lymphocytes, their subpopulations CD4+T-helpers, CD8+T suppressors, as well as CD25+ regulatory T-cells in newborns with the implementation of IUI. The activity of cytotoxic natural killer cells (CD16+NK), which implement anti-infective protection, was higher in the main groups than in the control, which is apparently due to the effect on the fetus of a large number of antigens. The percentage of B-lymphocytes in the umbilical blood of newborns with infectious abnormalities was in the range of reference values, but in Group I-0 of newborns the number of cells producing immunoglobulins was significantly higher than in the same group with the implementation of IUI, which may be associated with increased production of own immunoglobulins due to insufficient transplacental transfer of IgG from the mother. The increased concentration of IgM in the umbilical blood, which was found in various clinical groups, indicates the activation of humoral responses in the newborn in response to an infectious agent and is a marker of IUI. In the groups with IUI implementation, the concentration of IgM and IgG in the umbilical blood was lower by 20–30% and 13–17%, respectively, than in similar comparison groups, which is an important factor in reducing the anti-infective resistance of newborns. The level of IgA in the clinical groups did not differ statistically, although it exceeded the reference values. Conclusion. The functional activity of umbilical blood phagocytes in groups with clinical manifestations of IUI was characterized by a significant decrease in the ability of neutrophilic umbilical blood granulocytes to actively absorb and fully digest antigens. Such a defect in the phagocytic protection of the fetus may be one of the probable factors increasing the risk of infection. DOI: 10.5281/zenodo.4382178